PENDEKATAN SOSIAL KEPARIWISATAAN SEBAGAI UPAYA PENGEMBANGAN PARIWISATA DALAM RANGKA MENINGKATKAN PEREKONOMIAN DI PULAU MARINGKIK - Nadiawati, Baiq Saopi; Hasanah, Indri Annisa; Firdaus, Hana Kaori; Febriantari, Sabrina Evi; Raharja, Lalu Bayu Sagara Kusna; Majdi, M. Zainul; Zulkifli, Zulkifli; Humairo, Putri Zahratul; Elmi, Zaetun (Jurnal Wicara, 2023)
Tourism is one of the sectors that can boost the Indonesian economy. Lombok is an island located in the western southeast of Nusa that is famous for the beauty of its coast. The village of Maringkik Island, located in the East Lombok district, is the only island tourist village in Eastern Lombok. Maringkik Island has tourist potential, but is not optimally managed. This is due to several factors such as the historical and cultural influence of local communities, the lack of public awareness of the benefits of tourism development, and the minimal support of the village government. The purpose of this dedication is to raise the knowledge of the village of Marigkik in the field of tourism, to develop the tourism of Maringkik Island, to promote tourism on the island of Marinkik through the mass media and social media, and to improve the economy of the people of the island through the development of the tourist sector. The methods of implementation of the activities include (1) preparation of supplies; (2) planning including location surveys, and preparing the work programme listed in the proposal; (3) implementation includes photography of the island of Maringkik, basic English language training, socialization to increase knowledge about tourism development, beach clean, making tour packages, and the creation of websites and social media as well as video promotion for the tourism of the islands; (4) monitoring includes discussions with the village government, pokdarwis, and local communities related to the development of tourism and evaluation aimed at seeing the results achieved after monitoring. Besides, the KKN group is also involved in other activities, namely teaching activities. From the results of the observations carried out by the KKN team obtained information about some problems related to the development of tourism in Maringkik Island, then the result of the activities conducted at KKN PMD this shows that the activities of KKN-T, has been able to answer some problems and needs of the community and as an effort in developing tourism on the maringkik island.